High-Yield Fabrication of Ag Films by Reel-to-Reel Pulsed Laser Deposition System. (September 2019) - Matsuzaka, Jin; Tsuchiya, Yuji; Ichino, Yusuke; Yoshida, Yutaka
Abstract: Ag films are deposited on REBCO tapes as a stabilizing layer by a sputtering method in the most case. The sputtering deposition has a disadvantage of material cost for wasted Ag due to a low deposition yield, contrary to the pulsed laser deposition (PLD) method. Therefore, we developed Reel-to-Reel PLD system to fabricate Ag films on tapes with the high deposition yield. As results, the PLD method has a deposition rate up to 1 nm/s as the sputtering method. The electrical resistivity of the Ag film by the PLD method is 4.7 times higher than the sputtering method. The deposition yield of the PLD method is 13 times higher than the sputtering method. Finally, the Ag film was deposited on moving tapes by using the developed Reel-to-Reel PLD system with a uniform thickness.